Network programming with Go language : essential skills for programming, using and securing networks with open source Google Golang - Newmarch, Jan; Petty, Ronald (Apress, 2022)
Dive into key topics in network architecture implemented with the Google-backed open source Go programming language. Networking topics such as data serialization, application level protocols, character sets and encodings are discussed and demonstrated in Go. This book has been updated to the Go version 1.18 which includes modules, generics, and fuzzing along with updated and additional examples. Beyond the fundamentals, Network Programming with Go, Second Edition covers key networking and security issues such as HTTP protocol changes, validation and templates, remote procedure call (RPC) and REST comparison, and more. Additionally, authors Ronald Petty and Jan Newmarch guide you in building and connecting to a complete web server based on Go. Along the way, use of a Go web toolkit (Gorilla) will be employed. This book can serve as both an essential learning guide and reference on networking concepts and implementation in Go. Free source code is available on Github for this book under Creative Commons open source license.